Perubahan Klasifikasi Metafora Pada Novel Laskar Pelangi Karya Andrea Hirata Versi Bahasa Jepang Berdasarkan Fungsi Kognitifnya - Irwan Irwan; Muhammad Pujiono (KIRYOKU, 2019)
(The Changes of Metaphor Classification in Laskar Pelangi Novelby Andrea Hirata Japanese Language Version BasedonTheir Cognitive Functions) This article analyzed the changes in the classification of metaphorical expressions contained in the Laskar Pelangi novel based on their cognitive functions after being translated into the Japanese version. The theory used in this research is the classification theory of metaphor based on its cognitive function proposed by Kovecses (2010). This study uses a qualitative research approach with a descriptive type of research, while the method and data analysis uses interactive data analysis models from Miles, Huberman and Saldana (2014). The results of the data analysis showed that of 505 data found, there were 15 classifications of metaphor changes based on their cognitive functions, they are structural metaphors changed to structural metaphors consist of  95 data (18.8%), ontological metaphors to ontological metaphors consist of 151 data (29.9%), orientational metaphors to orientational metaphors consist of  5 data (1.0%), structural metaphor became ontological metaphor consist of 11 data (2.2%), structural metaphor became orientational metaphor consist of 2 data (0.4%), structural metaphor became simile consist of 2 data (0, 4%), structural metaphor becomes non-metaphoric consist of 67 data (13.3%), structural metaphor that was not translated consist of 4 data (0.8%), ontological metaphor became structural metaphors consist of 21 data (4.2%), ontological metaphor became orientational metaphor consist of 5 data (1,0%), ontological metaphor became simile consist of 10 data (2.0%), ontological metaphor became non metaphoric expression consist of 102 data (20.2%), untranslated ontological metaphor consist of 21 data (4.2%), orientational metaphor became non-metaphorical consist of 8 data (1.6%), and orientational metaphor became simile consist of 1 data (0.2%).